Traumatic disease peculiarities course, its diagnostics and treatment at polytrauma in suffer obese patients - Khimich, S. D.; Chemerys, O. M. (Modern medical technology, 2019)
Introduction. It’s known that the issue of polytrauma is one of the most urgent problems of surgery, and among injured patients a special approach is required for patients with overweight and obesity of varying degrees. Purpose of the study. To study prognostic features of traumatic disease course and to improve the results of diagnostics and surgical treatment of patients with polytrauma suffer obesity. Materials and methods. Clinical material was made up of 106 patients with combined body trauma, which were divided into three groups according to body mass index. Results. The results of the research showed a significant difference in the course of traumatic disease in patients with normal body weight and obesity. In particular, in the process of diagnostics of blunt chest and abdominal trauma the frequency of application of interventional methods of diagnostics was directly proportional to the increase of body mass index. The course of traumatic disease in the obese patients had a number of characteristic features that formed the basis for the development of diagnostics and differential program of treatment. Conclusions. The results of the research showed that the course of traumatic disease in combined injury obese patients is directly proportional to the body mass index and has certain features that differentiate them from patients with normal body weight.